Lepidoptera of North America 16. Butterflies of the Sierra Nevada - Davenport, Ken, author; C.P. Gillette Museum of Arthropod Diversity, publisher (Colorado State University. Libraries, 2020)
This publication covers the butterfly fauna of the Sierra Nevada mountain range in eastern California and a small area of the Carson Spur in western Nevada. At present (2019), 192 species, 104 subspecies and 15 segregates are known to have occurred within the range at least twice. Five additional species have been recorded at least once in the Sierra Nevada. This publication covers distributions of these butterflies within the Sierra Nevada and three National Parks, their habitats, flight periods and taxonomic issues based on current knowledge.
Butterflies of the Sierra Nevada
March 10, 2020.
Keywords: Lepidoptera -- California -- Sierra Nevada; Butterflies -- California -- Sierra Nevada; Lepidoptera -- Nevada -- Sierra Nevada; Butterflies -- Nevada -- Sierra Nevada